FAKTOR-FAKTOR YANG MENDUKUNG ASPIRASI KARIR DENGAN ADANYA MINAT BAKAT DAN PRESTASI AKADEMIK TERHADAP SISWA KELAS 12 - Rahmawati, Novrita; Rambe, Annisa; Gunasetiawan, Yogi (LPPM Universitas Awal Bros, 2024)
The final period of senior high school (SMA) is a crucial period for 12th grade students in determining their college majors that affect their future careers. This study aims to analyze the factors supporting career aspirations, including interests and talents, academic achievement, parental influence, peer influence, and information about majors. With a quantitative approach using a survey, the study involved 36 12th grade students at MA Masmur Pekanbaru. The results showed that interests and talents were the dominant factors influencing students' career aspirations, while parental influence and academic achievement contributed significantly but less. Information about majors had a significant influence in helping students make decisions, while peer influence was found to be statistically less significant. This study recommends the importance of multidimensional support, especially through interest and talent-based counseling, to help students make more mature career decisions.